Ketahanan balistik plat aluminum berlubang – komposit serat kevlar akibat impak proyektil bentuk hemispherical - Fadly, M.S. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2023)
This study examines the influence of hole diameter on the ballistic resistance of deformable 9 mm full metal jacket (FMJ) calibre projectiles. Both experimental and numerical findings reveal an effective mechanism for overcoming perforated aluminium plate and kevlar fibre composite. The results from experiments and simulations demonstrate that a 3 mm hole diameter can impede the bullet's velocity by penetrating the first and second layers, consequently impacting the back plate that forms a bulge. A hole with a diameter of 5 mm causes projectiles to be perforated with a residual velocity of 20.041 m/s. The 3 mm hole induces a bending effect on the projectile, leading to a deviation from its original trajectory.